Self-Regulated Learning and Prestasi Akademik Siswa Program Akselerasi Berdasarkan Jenis Kelamin - Siti Fatimah (Universitas Kanjuruhan Malang, 2019)
The study aimed to examine the correlation between self-regulated learning (SRL) and academic achievement; examine the correlation between cognitive, motivational, and behavioral regulations on academic achievement; and examine the difference of SRL level and academic achievement on male and female students of accelerated program in Senior High School of Malang. To analyze the data correlation of Pearson, multiple regression and t-test were applied. The findings revealed that 1) there was a significant positive correlation between SRL and academic achievement (r=.777); 2) there was a significant correlation between motivational and behavioral regulations and academic achievement, and 3) there was no significant difference between SRL level and academic achievement on male and female students on an accelerated program.